Between Domestic Care, Feelings, and Politics. The Correspondence of Bianca Maria Visconti (1450-1468) Tra cure domestiche, sentimenti e politica. La corrispondenza di Bianca Maria Visconti (1450-1468) - Maria Nadia Covini (Reti Medievali Rivista, 2009)
Bianca Maria Visconti duchess of Milan left behind her «a flood of correspondence», composed by either private letters, either dispatches of public interest. Her involvement in public affairs was not limited to the periods of regency, and she could dispose of a group of skilful secretaries (a part of her large household) to which she committed the writing of her letters. Her correspondents belonged either to her family − her husband, sons and daugters, relatives, more devote courtiers − either to her impressive patronal network, as ladies-in-waiting, friends, servants, retainers, nobles and aristocrats, prelates and even common people. In particular, the article reconsiders the last correspondence between the duchess and her son Galeazzo Maria, then duke of Milan: these letters reveal a warm personal affection, as much as a deep disagreement about the ruling of public affairs, and fully enlighten the strong temperament of this passionate Renaissance lady. The analysis finally focuses on some comments about the style, the formats, the literary solutions of the letters: for example, the use of autography to establish a closer contact with the correspondent. Bianca Maria Visconti, duchessa di Milano, lasciò una enorme quantità di corrispondenza depositata negli archivi milanesi, sia di carattere privato, sia pubblico e politico. Il suo coinvolgimento negli affari di stato non si limitò ai brevi periodi di reggenza, e grazie a un manipolo di segretari esperti e fedeli, che erano una parte della sua vasta «domus», potè dialogare a distanza con molti interlocutori: membri della sua famiglia e parenti, cortigiani devoti, nobili amici, e con con tutti coloro che facevano parte del suo personale reticolo di protetti e fedeli: dame di corte, servitori, fornitori, ecclesiastici e anche persone umili che si affidavano alla sua protezione. In particolare, viene qui riconsiderata e riletta la corrispondenza degli ultimi mesi di vita con il figlio duca Galeazzo Maria Sforza: da queste lettere traspare la profondità degli affetti tanto quanto il duro scontro tra i due principi circa la conduzione degli affari di stato. Alcune osservazioni sono infine dedicate allo stile, agli schemi di scrittura, alle soluzioni letterarie: per esempio, l’uso dell’autografia come mezzo per stabilire un contatto più intimo con il corrispondente.